Pollen viability and its effect on fruit set of oil palm (Elaeis guineensis Jacq.) - ALFIN WIDIASTUTI; ENDAH RETNO PALUPI (Society for Indonesian Biodiversity, 2008)
The research was aimed at studying (1) the decline of pollen viability during storage, and (2) the effect of pollen amount on fruit set of oil palm (Elaeis guineensis Jacq.). The experiment was conducted at PT. Dami Mas Sejahtera and PT. Sinar Mas Agro Resource and Technology (SMART) Tbk, Riau from February to August 2004. The first experiment was investigated up to six months storage period in the refrigerator, whereas in the second experiment a randomized complete block design with two factors was used: length of storage, i.e. 0, 1 and 2 months and amount of pollen, i.e. 0.022, 0.044, 0.066, 0.088, and 0.11 g mixed with powder to 10g to pollinate an inflorescence. The result showed that the viability of pollen started to decline three months after storage from about 92% to 83%, and declined to about 75% after six months of storage. Result of the second experiment showed that storage of pollen up to two months did not affect percentage ofnormal fruit, although the percentage of parthenocarpic fruits was decreased. This could be due to the high viability of pollen as the viability was remained high (about 90%) after being stored for two months in the refrigerator. Pollen with high viability could be used in a smaller amount to pollinate a female inflorescence without affecting fruit set of about 70-76%.SD037 had a higher reproductive success than SD038 and SD39.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: pollen storage, fruit set, amount of pollen, oil palm, Elaeis guineensis